Alcohol marketing on YouTube: exploratory analysis of content adaptation to enhance user engagement in different national contexts - Himanshu Gupta; Tina Lam; Simone Pettigrew; Robert J. Tait (BMC, 2018)
Abstract Background We know little about how social media alcohol marketing is utilized for alcohol promotion in different national contexts. There does not appear to be any academic work on online exposure to alcohol marketing via social media in India, and most of the limited research in Australia has focused on Facebook. Hence, the present study extends previous research by investigating alcohol promotion conducted on an under-researched form of social media (YouTube) in two contrasting geographic contexts. This study examines and compares the types of strategies used by marketers on Indian and Australian alcohol brands with the greatest YouTube presence, and the extent to which users engage with these strategies. Methods The 10 alcohol brands per country with the greatest YouTube presence were identified based on the number of 'subscriptions'. The number of videos, views per video, and the type of content within the videos were collected for each brand. The data were analyzed using an inductive coding approach, using NVivo 10. Results The targeted brands had gathered 98,881 subscriptions (Indian brands: n = 13,868; Australian brands: n = 85,013). The type of marketing strategies utilized by brands were a mix of those that differed by country (e.g. sexually suggestive content in India and posts related to the brand's tradition or heritage in Australia) and generic approaches (e.g. encouraging time- and event-specific drinking; demonstrations of food/cocktail recipes; camaraderie; competitions and prize draws; and brand sponsorship at music, sports, and fashion events). Conclusions This cross-national comparison demonstrates that YouTube provides alcohol marketers with an advertising platform where they utilize tailored marketing approaches to cater to specific national contexts and develop content on the cultural meanings users invoke in their interactions with these strategies. Those exposed to alcohol marketing on YouTube are likely to include those under the legal drinking age.